Penerapan Kode Etik Aparatur Sipil Negara dalam Penyelesaian Sengketa Kepegawaian : Studi Kasus Putusan Pengadilan Tata Usaha Negara Yogyakarta Nomor 10/G/2024/PTUN.YK - Pahri Ginanjar; Suwari Akhmaddhian (Uniku Law Review, 2025)
This study aims to examine how the regulation and implementation of the Civil Service (ASN) code of ethics applies in practice, particularly in resolving personnel disputes through the state administrative court mechanism. The author used a normative juridical research method with a case study of the Yogyakarta State Administrative Court Decision Number 10/G/2024/PTUN.YK. Data were analysed using Lawrence M. Friedman's Legal System Theory, which consists of elements of legal structure, legal substance, and legal culture. The results show that although a comprehensive regulatory framework regarding the ASN code of ethics is available, its implementation still faces obstacles related to the lack of synchronisation between agency authority, ASN's understanding of ethics, and a bureaucratic culture that does not fully support ASN professionalism and neutrality. The Yogyakarta State Administrative Court decision in this case confirms the crucial role of judicial oversight in testing the objectivity of administrative decisions based on violations of the code of ethics. In conclusion, resolving personnel disputes through the PTUN is an essential part of the legal system that ensures that personnel decisions do not deviate from the rule of law and the principles of bureaucratic ethics.